Respon masyarakat dan dampak lingkungan terhadap peternakan Babi di Kampung Inden II dan wilayah sekitar Pasar Kenangan Distrik Ransiki Kabupaten Manokwari Selatan: People’s response to and environmental impact of Pig farms in Inden II Village and the surrounding areas of Kenangan Market of Ransiki Subdistrict of South Manokwari District - Nathalya E.M. Sara; A. P. E. Widodo; Trisiwi W. Widayati (Fakultas Peternakan Universitas Papua, 2022)
Abstract The study aimed at finding out people’s response to and environmental impact of pig farms in Inden II village and the surrounding areas of Kenangan market of Ransiki subdistrict of South Manokwari district. It was descriptive study that used observation technique to generally describe the people’s response to the pig farm in Inden II village and the surrounding areas of Kenangan market of Ransiki subdistrict. Population and sample were classified into 2: pig farmers and those who were affected by the pig farm. The total number of the villagers of Inden II village and the surrounding areas of Kenangan market was 58 households, with the number of the pig farmers of 12 households so that there were 46 households of the population that did not do pig farming and were affected by the pig farms and recruited as respondents. The observed variables included people’s response to sub-variable of smell with following indicators: smelly (1) and smelly/long lasting (2); sub-variable of sound with following indicators: loud (1) and very loud/continuous (2); sub-variable of waste management with following indicators: feces were left unprocessed and scattered in various places, pig feed remnant and waste unprocessed and scattered; sub-variable of the number of pigs with following indicators: environment cleanliness (1) and riding or driving and walking comforts (2). They were measured using five points Likert scale: very annoying (5), annoying (4), annoying enough (3), not annoying (2) not very annoying (1). The results of the study showed that 58.69% of the people were very annoyed by the smell of the pig farms, 60.87% of them were very annoyed by the loud sound of the pigs, 45.65% of them were very annoyed by the continuous sound of the pigs, 47.83% of them were very annoyed by the number of the pigs that produced wastes affecting environmental cleanliness, and 45.65% of them were very annoyed by the feces of the pigs left unprocessed and scattered in various places. Keywords: Environmental impact; People’s response; Pig farm Abstrak Penelitian ini bertujuan untuk mengetahui respon masyarakat dari usaha peternakan babi terhadap dampak lingkungan di Kampung Inden II dan Sekitar Wilayah Pasar Kenangan Distrik Ransiki Kabupaten Manokwari Selatan. Jenis penelitian ini ialah jenis penelitian deskriptif dengan teknik observasi menjelaskan secara umum bagaimana respon masyarakat terhadap usaha peternakan babi di Kampung Inden II dan Wilayah sekitar Pasar Kenangan Distrik Ransiki. Jumlah populasi dan sampel dikelompokan menjadi 2 kelompok yaitu Masyarakat Peternak dan Masyarakat terkena dampak. Jumlah total masyarakat yang tinggal di Kampung Inden II dan wilayah sekitar pasar Kenangan yaitu sebanyak 58 Kepala Keluarga dengan jumlah peternak babi sebanyak 12 kepala keluarga sehingga jumlah populasi yang tidak beternak babi atau terkena dampak yaitu sebanyak 46 kepala keluarga sebagai responden. Variabel pengamatan yaitu Respon masyarakat terbagi atas subvariabel Penciuman (Aroma) dengan indikator berbau, berbau/tidak mudah hilang (2); Suara (Pendengaran) dengan indikator Sangat keras, Sangat Keras/Terus menerus; Penanganan Limbah indikator feses dibiarkan/tersebar diberbagai tempat, Sisa pakan dan sampah berantakan; Jumlah Ternak dengan indikator Kebersihan Lingkungan, Kenyamanan berkendara dan berjalan kaki. Pengukuran menggunakan skala Likert dengan kategori sangat terganggu (5), terganggu (4), cukup terganggu (3), tidak terganggu (2) dan sangat tidak terganggu (1). Hasil penelitian menunjukkan 58,69% sangat terganggu dengan bau yang ditimbulkan dari peternakan babi, 60,87% sangat terganggu dengan suara keras yang ditimbulkan, 45,65% masyarakat sangat terganggu dengan suara terus-menerus yang disebabkan oleh ternak babi, 47,83% merasa sangat terganggu oleh jumlah ternak yang mengganggu kebersihan lingkungan dan 45,65% masyarakat merasa sangat terganggu oleh feses yang dibiarkan dan tersebar diberbagai tempat. Kata Kunci: Dampak lingkungan; Peternakan babi; Respon masyarakat